TRANSFORMASI PENDIDIKAN DASAR DI ERA SOCIETY 5.0 : ANALISIS RELEVANSI, ADAPTASI KURIKULUM, DAN TANTANGAN IMPLEMENTASI - Muhammad Ihsan Ramadhani (Yayasan Pendidikan Literasi Borneo, 2025)
The era of Society 5.0 marks a significant paradigm shift in education, where digital technology, artificial intelligence (AI), and the Internet of Things (IoT) have become integral to learning processes. This study aims to analyze the relevance, curriculum adaptation, and implementation challenges of transforming elementary education in response to the demands of this new era. Using a qualitative approach based on literature review, data were collected from scientific journals, books, and educational policy documents published between 2020 and 2025. The findings reveal that the transformation of elementary education in Indonesia requires strengthening teachers’ digital competencies, developing adaptive curricula aligned with the “Profil Pelajar Pancasila,” and integrating humanistic values in the use of technology. However, challenges remain in terms of infrastructure readiness, teacher training, and the digital divide across regions. Therefore, a collaborative strategy involving the government, educational institutions, and communities is essential to ensure that elementary education is not only technologically oriented but also grounded in character building and human values. This transformation is expected to foster a generation of learners who are creative, adaptive, and globally competitive in the Society 5.0 era.